Mission as transformation - Samuel, Vinay (Regnum studies in mission., 2019)
Mission as Transformation: A Theology of the Whole Gospel brings together in one volume twenty-five years of biblical reflection on mission practice with the poor from around the world. The whole gospel is centered on the rule of Christ over the whole of life. It seeks to impact a community with the values and the spiritual challenges of the kingdom of God. The key to holistic ministry is enabling people to experience Christ's Lordship. Holistic mission integrates proclamation, evangelism, church planting, and social transformation in a seamless whole. This approach to Christian mission has been adopted since 1983 by most evangelical agencies involved in development, and by most Indigenous mission agencies involved with transforming the lives of the communities with whom they work. It also represents the approach of many Pentecostal churches. Mission as transformation has been a struggle for evangelicals. Our Two-Thirds World colleagues have patiently assisted many of us to the table. This book provides a gathering place for the seminal papers and discussions that are part of this twenty-five-year journey, and will help readers understand how evangelicals, struggling to unite evangelism and social action, found their way to the biblical view of mission in which God calls all human beings to love God and their neighbor, never creating a separation between the two.